Quality in care requires kindness and flexibility - a hermeneutic-phenomenological study of patients' experiences from pathways including transitions across healthcare settings - Sisse Walløe; Malene Beck; Henrik Hein Lauridsen; Lars Morsø; Charlotte Simonÿ (BMC, 2024)
Abstract Background The number of people living with chronic conditions is increasing worldwide, and with that, the need for multiple long-term complex care across care settings. Undergoing transitions across healthcare settings is both challenging and perilous for patients. Nevertheless, knowledge of what facilitates quality during transitions in healthcare settings from the lifeworld perspective of patients is still lacking. Therefore, we aimed to explore the lived experience in healthcare quality for Danish adult patients during healthcare pathways including transitions across settings. Methods Within a hermeneutic-phenomenological approach, interviews were conducted with three women and five men with various diagnoses and care paths between 30 and 75 years of age. Data underwent a three phased thematic analysis leading to three themes. Results Patients with various illnesses' experiences of quality of care is described in the themes being powerless in the face of illness; burdensome access and navigation; and being in need of mercy and striving for kindness. This highlights that patients' experiences of quality in healthcare pathways across settings interweaves with an overall understanding of being powerless at the initial encounter. Access and navigation are burdensome, and system inflexibility adds to the burden and enhances powerlessness. However, caring care provided through the kindness of healthcare professionals supports patients in regaining control of their condition. Conclusions This hermeneutical-phenomenological study sheds light on the lived experiences of people who are at various stages in their care paths with transitions across healthcare settings. Although our findings are based on the lived experiences of 8 people in a Danish context, in light of the discussion with nursing theory and other research, the results can be reflected in two main aspects: I) kind and merciful professional relationships and II) system flexibility including access and navigation, were essential for their experiences of care quality during healthcare transitions. This is important knowledge when striving to provide patients with a clear voice regarding quality in care pathways stretching across settings.